A variable structure algorithm using the (3,2)-scheme and the Fehlberg method - Novikov, E.A. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2015)
A third-order (3,2)-method allowing freezing the Jacobi matrix is constructed. Its main and intermediate numerical schemes are L-stable. An accuracy control inequality is obtained using an embedded method of second order. A stability control inequality for the explicit three-stage Runge-Kutta-Fehlberg method of third order is proposed. A variable structure algorithm is formulated. An explicit or L-stable method is chosen according to the stability criterion at each step. Numerical results are discussed.